Law and the media the future of an uneasy relationship - Gies, Lieve (Routledge-Cavendish, 2008)
Introducing readers to the study of law, media and popular culture, this text, using three case studies, re-examines the assumptions underpinning research and suggests alternatives. Exploring the uneasy relationship between law and popular culture from specific socio-legal perspectives, it is useful for those studying and researching in this area.